2004
DOI: 10.1136/bmj.38041.493519.ee
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nurse practitioners on workload of general practitioners: randomised controlled trial

Abstract: Objective To examine the impact on general practitioners' workload of adding nurse practitioners to the general practice team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 11 publications
3
74
1
6
Order By: Relevance
“…65 However, a randomised trial indicated that nurse practitioners supplement rather than substitute for doctors with whom they work, while providing a wider range of services. 66 There is less systematic evidence available on the quality of care provided in low resource settings. In a retrospective cohort analysis of patients in a Mozambican HAART program, outcomes were similar for MLWs and doctors.…”
Section: Quality Of Carementioning
confidence: 99%
“…65 However, a randomised trial indicated that nurse practitioners supplement rather than substitute for doctors with whom they work, while providing a wider range of services. 66 There is less systematic evidence available on the quality of care provided in low resource settings. In a retrospective cohort analysis of patients in a Mozambican HAART program, outcomes were similar for MLWs and doctors.…”
Section: Quality Of Carementioning
confidence: 99%
“…This finding is of particular importance because it pinpoints to the fact that nurses are not sufficiently satisfied and several studies have reported a strong influence of the satisfaction of nonphysician staff to patient satisfaction [2,4]. As one study reported, in general practice, nurses are commonly considered as supplements rather than substitutes for the care given [15] and this might influence their overall satisfaction.…”
Section: Discussionmentioning
confidence: 96%
“…They work in collaboration with family physicians, specialists, or both. [14][15][16][17][18][19][20][21][22] Over the last few years, several systematic reviews have found that the evidence of CM's effects on service use and clinical outcomes is weak. [23][24][25][26][27][28] None of them specifically focused on the needs of patients and caregivers, however.…”
mentioning
confidence: 99%
“…Fixed-effects models were used because of the small sample size (2 in each outcome evaluation). 16,17,19,21,22 and problematic home situations.18 They counseled on available resources/ services, 16,20 legal and financial issues, and advance directives.14-16 Finally, case managers coordinated medical and community services via electronic, written, and case conference discussion. [14][15][16][17]19,20 To meet the needs of patients, case managers applied, in collaboration with family physicians, nonpharmacologic and pharmacologic protocols for management of daily activities, [14][15][16] behavior distress, [14][15][16]21,22 cognition, 14-16 mood, [14][15][16] and home safety.…”
mentioning
confidence: 99%
See 1 more Smart Citation